Dihydroartemisinin-piperaquine rescue treatment of multidrug-resistant Plasmodium falciparum malaria in pregnancy: a preliminary report. - Rijken, M; Mcgready, R; Boel, M; Barends, M; Proux, S; Pimanpanarak, M; Singhasivanon, P; Nosten, F (2008)
Dihydroartemisinin-piperaquine (DHA-PPQ) is a promising new artemisinin combination treatment. There are no published data on the intentional use of the drug in pregnancy. Between June 2006 and January 2007, 50 Karen pregnant women with recurrent P. falciparum infections, despite 7-day treatments with quinine or artesunate (+/-clindamycin) or both, were treated with DHA-PPQ. This rescue treatment was effective and well tolerated and there was no evidence of toxicity for the mothers or the fetus. The PCR adjusted cure rate by Kaplan Meier analysis at day 63 was 92.2% (95% CI: 76.9-97.4).